An Economic Study of the Reality of Sesame Cultivation in Iraq - Abdullah, Dawood Fahad (American Journal of Biodiversity, 2026)
The study aims to examine the trends of industrial sesame area, production, yield, and prices in Iraq from 1990 to 2023. The results showed that the average area of industrial sesame cultivation exceeded 14,000 hectares, the average production exceeded 11,000 tons, the average yield exceeded 6,000 kg/hectare, and the average price exceeded 1,400 Iraqi Dinars. The results showed that the growth rates of area, production, yield, and prices were 6.2%, 5.3%, 2.8%, and 4.2%, respectively. However, the study showed a decline in industrial sesame production due to the increase in the cost of production, the government’s weak support, and the ineffectiveness of agricultural policies. The econometric model showed a high level of explanation of the independent variables (R2 = 0.89). The results showed that the cultivated area (0.897) and the price index (0.714) had a statistically significant positive effect on industrial sesame production at the 5% level of significance. However, the results showed a statistically insignificant negative effect of the yield (-0.098). The diagnostic tests showed the validity of the model and the absence of autocorrelation and multicollinearity. The results of the study showed the importance of providing incentives through prices, increasing the area of industrial sesame cultivation, and the need to implement flexible agricultural policies to support investment in sesame production in Iraq.